2019
DOI: 10.1371/journal.pone.0209970
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of mini-laparotomy in patients with colorectal cancers: A propensity scoring matching approach

Abstract: ObjectiveSurgical technique process innovations are expected to generally incur no additional cost but gain better quality. Whether a mini-laparotomy surgery (MLS) in the treatment of colorectal cancer (CRC) is more cost effective than conventional open surgery had not been well examined. The objective of this study was to apply cost-effectiveness approaches to investigate the cost effectiveness of adopting MLS compared with open surgery 1 year following resection in CRC patients.Research designA prospective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In recent years, an increasing number of studies have reported the clinical benefits of mini-laparotomies for colorectal cancer resection. Different authors defined a mini-laparotomy as an abdominal wound length either less than 7 or 8 cm (17)(18)(19)(20). Regardless of the mild difference in wound length, the minilaparotomy was significantly associated with earlier recovery of flatus passage than a conventional laparotomy (17,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, an increasing number of studies have reported the clinical benefits of mini-laparotomies for colorectal cancer resection. Different authors defined a mini-laparotomy as an abdominal wound length either less than 7 or 8 cm (17)(18)(19)(20). Regardless of the mild difference in wound length, the minilaparotomy was significantly associated with earlier recovery of flatus passage than a conventional laparotomy (17,20).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mild difference in wound length, the mini-laparotomy was significantly associated with earlier recovery of flatus passage than a conventional laparotomy ( 17 , 20 ). A recent case-controlled study comparing the medical costs of a mini-laparotomy (less than 8 cm) and a conventional laparotomy in patients with colorectal cancer reported that the mini-laparotomy is more cost-effective because of fewer complications and a shorter post-operative hospital stay ( 19 ). Thus far, the biological mechanism underlying the benefits of mini-laparotomy abdominal wounds on the earlier recovery of flatus passage or shorter hospital stay remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mild difference in wound length, the minilaparotomy was significantly associated with earlier recovery of flatus passage than a conventional laparotomy (17,20). A recent case-controlled study comparing the medical costs of a minilaparotomy (less than 8 cm) and a conventional laparotomy in patients with colorectal cancer reported that the mini-laparotomy is more cost-effective because of fewer complications and a shorter post-operative hospital stay (19). Thus far, the biological mechanism underlying the benefits of mini-laparotomy abdominal wounds on the earlier recovery of flatus passage or shorter hospital stay remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%